Not Able to Lead a Healthy Life When You Need It the Most: Dual Role of Lifestyle Behaviors in the Association of Blurred Work-Life Boundaries With Well-Being - Pluut, Helen; Wonders, Jaap (Frontiers in Psychology, 2020)
As there is a growing trend for people to work from home, precipitated by the COVID-19 pandemic, this research examines the impact of blurred work-life boundaries on lifestyle and subjective well-being. Our cross-sectional study in the Netherlands demonstrates that heightened levels of blurred work-life boundaries predict negative changes in happiness through enhanced emotional exhaustion. In addition, the findings point to a dual role of lifestyle in this process. On the one hand, we observed that healthy overall lifestyle patterns buffered employees against the detrimental effects of blurred work-life boundaries and emotional exhaustion on happiness. On the other hand, employees who experienced increases in blurring of work-life boundaries reported a deterioration in healthy lifestyle behaviors, which in turn was related to reduced happiness. Paradoxically, it seems that those who would benefit the most from a healthy lifestyle are less able to sustain health-promoting behaviors. A case for shared responsibility between employers and employees is built as we discuss the practical implications of the current research.